ANALISIS KUALITAS PELAYANAN DENGAN METODE SERVICE QUALITY (SERVQUAL) DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) PADA PT. MEDIA PURNA ENGINEERING - Heru Winarno; Tb Absor (Jurnal Manajemen Industri dan Logistik (JMIL), 2017)
PT. Media Purna Engineering is a company engaged in the field of mechanical maintenance services rotating, hydraulic systems, construction, and piping. PT. Media Purna Engineering has never conducted a measurement of the level of satisfaction of its partner companies so that in improving the quality of service and in overcoming the complaints have not been done properly. The purpose of this study is to improve the quality of service to the satisfaction of partner companies namely PT. Krakatau Steel (Persero) Tbk for the services provided. The research method used is the method of Service Quality (Servqual) and Importance Performance Analysis (IPA) to measure the level of satisfaction and quality of services provided .. Based on research results indicate that the quality of service PT. Media Purna Engineering is good, but there are 1 service quality attribute that still need to be improved or developed from 25 attribute of service quality, that is at the 15th attribute about speed in giving solution. Recommendations for improvement include the introduction of the work area, new workers should always be supervised and supervised, schedule training, constraints please quickly inform Lieder or Supervisor to be quick in providing solutions to overcome them.